Processes and Characterizations of Metal Matrix Composites - Pramanik, Alokesh; Zhang, L. (CRC Press, 2012)
Metal matrix composites (MMCs) have superior mechanical properties compared with their monolithic counterparts, and hence have had a wide range of applications in aeronautical and aerospace engineering. This chapter will discuss the properties of MMCs, their fabrication processes and their latest development. A focussed discussion will then be on their mechanical behaviour under some fundamental deformation modes, such as compression, tension and indentation. The application of MMCs requires precise shaping, thus the characterisation of the machinability of MMCs will be presented. Tool performance and machining outcomes will be described in detail associated with turning, milling and grinding operations in the manufacture of MMC components.